EFFECTS OF PARTICIPATION IN PHYSICAL TRAINING PROGRAM FOR PATIENT WITH PARKINSON'S DISEASE: A CASE REPORT - Souza, Aylin Ferreira; Braco, Sabrina; Biagiotto, Patricia; Nonato da Silveira, Marcelo Cesar; Assis, Welton Ferreira de [UNESP]; Higino, Wonder Passoni; Curiacos de Almeida Leme, Jose Alexandre (Univ Federal Uberlandia, 2016)
The aim of this study was to investigate the effects of physical activity in people with Parkinson's disease PD (case study). To this, a subject (54 years) participant of the PARKVIDA project performed physical exercise training 3 days/week. The intensity of physical activity was mild-moderate monitored by frequencimeter and consisted of aerobic exercises, strength and specific (motor coordination and balance) adapted from Gobbi's protocol. Before and after the period of 8 months were applied the tests: quality of life (SF-36), balance (unipodal support test), body composition, cardio respiratory fitness (spirometry) and a part of AAHPERD battery: coordination, agility, strength and flexibility. The results showed changes in physical aspects such as agility, balance, flexibility and coordination, concomitant with improvement in cardiorespiratory fitness and quality of life (dimension pain). In conclusion, this study suggests that changes promoted by physical activity can contribute to improve cardio respiratory conditioning, reducing the perception of pain and physical and motor improvements in patient with PD.
Keywords: Parkinson Disease; Physical exercise; Balance; Strength